Composition and structure of water beetles community (Insecta: Coleoptera) along an altitudinal gradient, Cusco, Peru - Huanachin Quispe, Agata (2018)
The aim of this paper was to know the composition and structure of water beetles community in different streams along a wide altitudinal gradient (476-4411 m altitude) in Cusco, Peru. For that, 12 sampling stations were established and two collects were carried out during May and July-August 2013 (dry season), in the running water and stony substrate. A total of 3069 individuals were collected between larvae and adults of aquatic beetles, belonging to 23 genera, grouped into 10 families. Elmidae presented the highest richness (13 genera) and abundance (90.4%), being distributed along the whole gradient. The most representative genera by abundance were: Austrelmis, Neoelmis, Heterelmis and Anchytarsus. The Wilcoxon-Mann-Whitney and Kruskall-Wallis non-parametric statistical tests for richness, abundance and community structure, clustering analysis (CLUSTER) and similarity analysis (ANOSIM) showed significant differences in the composition of the beetles community along the gradient studied. The percentage similarity analysis (SIMPER) allowed to identify the genera that most influenced the community structure, stand out Neoelmis and Heterelmis in stations located at low and medium altitude, and Austrelmis in stations of higher altitude. A positive correlation of temperature with the richness, diversity and equity, and a negative correlation with these variables altitude was evident.